Alberta Stroke Program Early CT Score Infarct Location Predicts Outcome Following M2 Occlusion - Khan, Muhib; Baird, Grayson L.; Goddeau, Richard P.; Silver, Brian; Henninger, Nils (Frontiers in Neurology, 2017)
Background: Although it is generally thought that patients with distal middle cerebral artery (M2) occlusion have a favorable outcome, it has previously been demonstrated that a substantial minority will have a poor outcome by 90 days. We sought to determine whether assessing the Alberta Stroke Program Early CT Score (ASPECTS) infarct location allows for identifying patients at risk for a poor 90 day outcome. Methods: We retrospectively analyzed patients with isolated acute M2 occlusion admitted to a single academic center between January 2010 to August 2012. Infarct regions were defined according to ASPECTS system on the initial head CT. Discriminant function analysis was used to define specific ASPECTS regions that are predictive of the 90 day functional outcome as defined as a modified Rankin Scale score of 3-6. In addition, logistic regression was used to model the relationship between each individual ASPECT region with poor outcome; for evaluation and comparison, odds ratios, c-statistics, and Akaike information criterion values were estimated for each region. Results: 90 patients with isolated M2 were included in the final analysis. ASPECTS score ≤ 6 predicted poor outcome in this cohort (sensitivity=0.591, specificity=0.838, p<0.001). Using multiple approaches, we found that infarction in ASPECTS regions M3 and M6 were strongly associated with poor functional status by 90 days. Conclusion: Infarction in ASPECTS regions M3 and M6 are key predictors of functional outcome following isolated distal M2 occlusion. These findings will be helpful in stratifying outcomes if validated in future studies.